Synthesis and Characterization of Activated Carbon/Alginate-Fe Composites as Slow Release Fertilizer - Panjaitan, Teguh Hidayat; Muchtar, Zainuddin; Rahmah, Siti; Zubir, Moondra; Pulungan, Ahmad Shafwan; Selly, Rini; Faradilla, Putri (Indonesian Journal of Chemical Science and Technology (IJCST), 2024)
Research on the slow release kinetics of Fe(III) ions from Activated Carbon/Alginate-Fe(III) composites or abbreviated as K/A-Fe(III) has been carried out. The aim of this research was to synthesize K/A-Fe(III) composite as a material that has the potential to become a slow release micronutrient fertilizer and to study the kinetics of slow release of Fe(III) ions from the composite. The K/A-Fe(III) composite was synthesized by mixing alginate suspension and activated carbon (alginate: activated carbon weight ratio = 1:3 and 3:1) until homogeneous. Composite grains were characterized using Fourier Transformed Infrared (FTIR) spectroscopy, the kinetics of Fe(III) release from the three composite variations found that KAlg31 composite showed more absorption and release of Fe ions than KAlg13.